perancangan pusat kuliner nusantara dengan konsep arsitektur kontemporer di kota malang jawa timu - Febriana, Khofifah; Kurniasih, Sri; Sulistyowati, Anggraeni Dyah (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2024)
The design of the Nusantara culinary center with a contemporary architectural concept is a place that provides facilities for culinary activities which not only include food but also various kinds of drinks which can be used as a recreation place for tourists and the local community. The application of the principles in the design of the Indonesian culinary center building is contemporary architecture such as having lots of openings, using neutral colors, and using glass material to maximize lighting, building orientation towards sunlight and the facade material is wood. This Indonesian culinary center is in the city of Malang because there are still minimal Indonesian culinary centers. With the existence of this Indonesian culinary center, it not only provides culinary specialties from the city of Malang, but also various kinds of traditional foods and foods that are currently trending in Indonesia so that tourists who come can experience the regional culinary specialties found in Indonesia.